Intraprocedural Back Pain Associated with Awake Neuroendovascular Procedures. Issue 1 (11th November 2020) - Qureshi, Adnan I.; Jahngir, Muhammad Umair; Akinci, Yasemin; Gao, Xiaoyu; Akhtar, Iqra Naveed; Kraus, Jacqueline; Singh, Baljinder; Lobanova, Iryna; Uzun, Guven; Balasetti, Vamshi K.S.; Liaqat, Jahanzeb; French, Brandi R.; et al.
ABSTRACT: BACKGROUND AND PURPOSE: The prevalence and characteristics of intraprocedural back pain is not well studied in awake patients undergoing neuroendovascular procedures. METHODS: We performed a prospective study as part of quality improvement initiative in which all patients who underwent neuroendovascular procedures in awake state were inquired regarding presence, severity (using a numeric rating scale score ranging from 0 [no pain] to 10 [worst pain possible]), and location (using anatomical chart) of back pain immediately after the procedure. The primary endpoint was the proportion of patients with moderate to severe pain (score of ≥3). RESULTS: A total of 100 (41.3%) of 242 patients reported intraprocedural back pain with a median severity of 5/10 (range 1‐10). The mean age was 58.7 ± 16.2 years. The mean duration of the procedure was 82.3 minutes (range 15‐410 minutes). The pain was classified as moderate to severe in 86 of 100 patients. The locations of pain were identified in lumbar ( n = 77), thoracic ( n = 6), cervical ( n = 7), cervical and lumbar ( n = 8), and cervical with thoracolumbar ( n = 2) regions. There was a significant relationship between patients' history of the previous neck and/or back surgery and frequency of moderate to severe back pain ( P  = .02). No significant relationship was observed between frequency of none to mild and moderate to severe back pain among the strata by patients' age, body mass index, or duration of procedures. CONCLUSIONS: The relatively high prevalence of intraprocedural back pain in patients undergoing neuroendovascular procedures in awake state must be recognized, and strategies to reduce the occurrence need to be identified.